Reevaluation of the post-marketing safety of Shuxuening injection based on real-world and evidence-based evaluations - Wang C; Shi QP; Ding F; Jiang XD; Tang W; Yu ML; Zhu JH (Dove Medical Press, 2018)
Can Wang,1,2 Qing-ping Shi,1,2 Feng Ding,2 Xiao-dong Jiang,1,2 Wei Tang,3 Mei-Ling Yu,1,2 Jian-Hua Zhu2 1Department of Pharmacy, The First Affiliated Hospital of Bengbu Medical College, Bengbu, People’s Republic of China; 2Faculty of Pharmacy, Bengbu Medical College, Bengbu, People’s Republic of China; 3Department of Pharmacy, Huaiyuan County Hospital of TCM in Anhui, Bengbu, People’s Republic of China Aim: To evaluate the factors influencing suspected hypersensitivity and adverse systemic reactions after Shuxuening injection and to provide innovative ideas and methods for the reevaluation of post-marketing safety of Shuxuening.Methods: This study used a prospective, nested case–control study design, combined with a prescription sequence analysis design method. It classified patients who exhibited trigger signals after administration of Shuxuening injection as suspected allergic patients and made comparisons with patients who did not report adverse effects to calculate the correlation between relevant risk factors and suspected allergic reactions. Randomized controlled studies and cohort studies of the adverse drug reaction (ADR) of Shuxuening were performed using a computer database. Data retrieval was carried out by the foundation governing the individual database. Meta-analysis was performed by using R3.2.3 software to evaluate the ADRs of Shuxuening.Results: The results of real-world study showed that administration of Shuxuening in combination with potassium aspartate and magnesium, atorvastatin calcium, Shengmai injection, pantoprazole sodium, or high-dose medication was a risk factor for suspected allergic reactions. Meta-analysis showed that the incidence of adverse events was 5.84% (95% CI 0.0499; 0.0674), and serious adverse reaction rate was 4.36% (95% CI 0.0188; 0.0760) when Shuxuening was used in combination with these drugs. The incidence of allergic reaction was also influenced by the vehicle, duration of treatment, single dose, and indicated vs off-label use.Conclusion: Risk factors for adverse reaction following the use of Shuxuening injection in patients are associated with a single dose, vehicle, type of disease, and combination with potassium aspartate, atorvastatin calcium, Shengmai injection, injection with pantoprazole sodium, and other drugs. Physicians should be careful to follow guidelines when administering this drug. We further propose that the unique methodology used in this study may be useful for reevaluation of the safety of other traditional Chinese medicines.Keywords: real-world study, evidence-based evaluation, Shuxuening injection, post-marketing safety reevaluation, allergic reaction